ANALISIS PERENCANAN PUTARAN BALIK (U-TRUN ) STUDI KASUS : JL. ALAMSYAH RATU PRAWIRA NEGARA KOTA PAGAR ALAM - Wijaya, Tommi; Sang, Gumilar Muhammad; Dyan, Pratnamas (Jurnal Teknik Sipil, 2019)
Transportation problems are problems that are always faced by developed countries and developing countries such as the city of fencealam, both in the economic and social fields. Planning a back-turn (u-turn) vehicle on a median road network greatly influences traffic conditions when the road network has a good performance, many benefits are gained by the community. The advantage is that it increases local income and income, especially for city railings. nature if road service, runs smoothly. The purpose of this study was to determine the dimensions of the median width and the placement of u-turn on the Alamsyah Ratu Prawira Negara City fencealam road segment. Primary data collection is carried out for 2 days, namely Sunday and Monday represents working days, namely Monday morning at 06.00-18.00 WIb The survey data is carried out including calculation of traffic volume, speed, capacity, degree of saturation, level of road service, complication at the intersection. Data analysis was carried out by tabulating data to obtain road characteristics, median ideal width, and total placement. From the results of calculations, the peak hour traffic volume was 183 smp / hour and Monday was 298 pcu / hour.